Uso do condicionamento operante como ferramenta de conservação ex-situ em instituições brasileiras - Moraes, Caroline Rodrigues de (Universidade Federal de São Carlos, 2026)
Operant conditioning has become established as a strategic tool in the management of wild animals kept in ex situ conservation programs. This study investigated the practical application of operant conditioning in Brazilian institutions (zoos, wildlife triage and rehabilitation centers, breeding facilities, among others), analyzing the profile of training protocols, their purposes, and the technical limitations faced. The methodology consisted of a literature review and the application of a diagnostic form, preceded by a pilot study to validate and refine the instrument, which was subsequently applied to 201 institutions, of which 29 responded (30 including the pilot).The results indicate that operant conditioning is widely used in Brazilian ex situ conservation institutions, being implemented in 70% of the participants and under development in an additional 16.7%. Its application is mainly concentrated on large mammals and birds, particularly felids, primates, and psittacine, revealing marked taxonomic selectivity to the detriment of reptiles and invertebrates. Operant conditioning is primarily employed to facilitate daily and veterinary management, promote animal welfare, and reduce the need for physical and chemical restraint, with a predominance of positive reinforcement techniques. Although most institutions report having trained professionals, the lack of specialized technical training and the absence of systematic behavioral assessments, such as the use of ethograms, represent significant limitations. It is concluded that, despite its strong potential as a management and conservation tool in Brazil, operant conditioning still requires greater technical standardization and broader taxonomic application to be consolidated as a robust strategy for animal welfare, rehabilitation, and wildlife release.
Use of operant conditioning as an ex-situ conservation tool in Brazilian institutions
Keywords: Bem-estar animal; Comportamento animal; Enriquecimento ambiental; Etograma; Animal behavior; Animal welfare; Environmental enrichment; Ethogram; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::CONSERVACAO DAS ESPECIES ANIMAIS; 15. Vida Terrestre; 14. Vida na Água